Room Temperature Formation of High‐Mobility Two‐Dimensional Electron Gases at Crystalline Complex Oxide Interfaces. (12th December 2013) - Chen, Y. Z.; Bovet, N.; Kasama, T.; Gao, W. W.; Yazdi, S.; Ma, C.; Pryds, N.; Linderoth, S.
<x xml:space="preserve">Abstract</x> Well‐controlled sub‐unit‐cell layer‐bylayer epitaxial growth of spinel alumina is achieved at room temperature on a TiO2‐terminated SrTiO3 single‐crystalline substrate. By tailoring the interface redox reaction, 2D electron gases with mobilities exceeding 3000 cm 2 V−1 s−1 are achieved at this novel oxide interface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>